Mobile-Genetic-Element-Encoded Hypertolerance to Copper Protects Staphylococcus aureus from Killing by Host Phagocytes - Marta Zapotoczna (American Society for Microbiology, 2018)
ABSTRACT Pathogens are exposed to toxic levels of copper during infection, and copper tolerance may be a general virulence mechanism used by bacteria to resist host defenses. In support of this, inactivation of copper exporter genes has been found to reduce the virulence of bacterial pathogens in vivo. Here we investigate the role of copper hypertolerance in methicillin-resistant Staphylococcus aureus (MRSA). We show that a copper hypertolerance operon (copB-mco), carried on a mobile genetic element (MGE), is prevalent in a collection of invasive S. aureus strains and more widely among clonal complex 22, 30, and 398 strains. The copB and mco genes encode a copper efflux pump and a multicopper oxidase, respectively. Isogenic mutants lacking copB or mco had impaired growth in subinhibitory concentrations of copper. Transfer of a copB-mco-carrying plasmid to a naive clinical isolate resulted in a gain of copper hypertolerance and enhanced bacterial survival inside primed macrophages. The copB and mco genes were upregulated within infected macrophages, and their expression was dependent on the copper-sensitive operon repressor CsoR. Isogenic copB and mco mutants were impaired in their ability to persist intracellularly in macrophages and were less resistant to phagocytic killing in human blood than the parent strain. The importance of copper-regulated genes in resistance to phagocytic killing was further elaborated using mutants expressing a copper-insensitive variant of CsoR. Our findings suggest that the gain of mobile genetic elements carrying copper hypertolerance genes contributes to the evolution of virulent strains of S. aureus that are better equipped to resist killing by host immune cells. IMPORTANCE Methicillin-resistant Staphylococcus aureus (MRSA) poses a substantial threat to human health worldwide and evolves rapidly by acquiring mobile genetic elements, such as plasmids. Here we investigate how the copB-mco copper hypertolerance operon carried on a mobile genetic element contributes to the virulence potential of clinical isolates of MRSA. Copper is a key component of innate immune bactericidal defenses. Here we show that copper hypertolerance genes enhance the survival of S. aureus inside primed macrophages and in whole human blood. The copB and mco genes are carried by clinical isolates responsible for invasive infections across Europe, and more broadly among three successful clonal lineages of S. aureus. Our findings show that a gain of copper hypertolerance genes increases the resistance of MRSA to phagocytic killing by host immune cells and imply that acquisition of this mobile genetic element can contribute to the success of MRSA.